Supramolecular Assembly of Peptide and Metallopeptide Gelators and Their Stimuli‐Responsive Properties in Biomedical Applications. Issue 54 (13th July 2018) - Falcone, Natashya; Kraatz, Heinz‐Bernhard
Abstract: Supramolecular gels are a fascinating class of soft materials that have attracted significant attention in recent years. They are composed of small molecule gelators that assemble into supramolecular network structures. The resulting space is filled with solvent. Some gel materials are able to respond to various stimuli making them attractive drug delivery vehicles and as matrices for tissue regeneration. Peptide‐based gel materials are particularly attractive as they possess numerous advantages including biocompatibility and biodegradability. Stimuli‐responsive peptides that alter properties as a function of pH, redox, temperature, and enzymes offer the potential to create materials with tunable characteristics. In addition, the ability of metal ions to improve the strength of gelation or act as a scaffold has become an interesting approach to develop dynamic peptide gel materials. In this review, the stimuli‐responsive properties (pH, redox, temperature, and enzyme responsive properties), as well as the biocompatible/‐degradable nature of the peptide gelators are highlighted. In addition, metal ions are discussed as a stimulus to enhance peptide gelation and a number of potential applications of these peptide gelators are provided with an outlook on future directions. Abstract : Stimuli‐responsive peptides and peptide conjugates are an interesting class of molecules that have a wide range of applications including drug delivery and tissue engineering. The rapid increase of the exploration of supramolecular hydrogels certainly promises future materials that will improve human health.